2019
DOI: 10.2174/1871523018666190222115034
|View full text |Cite
|
Sign up to set email alerts
|

Screening of NO Inhibitor Release Activity from Soft Coral Extracts Origin Palu Bay, Central Sulawesi, Indonesia

Abstract: Background: As a marine organism, soft corals can be utilized to be various bioactive substances, especially terpenoids and steroids. The soft corals family which produces bioactive generally come from clavulariidae, alcyoniidae, nephtheidae and xeniidae family.Objective: To investigate the bioactivity of Nitric Oxide (NO) inhibitor release from soft coral crude extracts of Sinularia sp. (SCA), Nephthea sp. (SCB), Sarcophyton sp. (SCC), Sarcophyton sp. (SCD), Sinularia sp. (SCE) and Sinularia sp. (SCF).Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 95 publications
0
10
0
9
Order By: Relevance
“…In previous studies, it was concluded that the three soft coral crude extracts used in this study had nitric oxide (NO) inhibitory release activity (Tanod, Yanuhar, Maftuch, Putra, & Risjani, 2019). Besides that, the three soft coral crude extracts showed DPPH scavenging properties at concentrations 10, 30, 50, 70, 90 g/mL (Tanod, Yanuhar, Maftuch, Wahyudi, & Risjani, 2019).…”
Section: Introductionmentioning
confidence: 63%
“…In previous studies, it was concluded that the three soft coral crude extracts used in this study had nitric oxide (NO) inhibitory release activity (Tanod, Yanuhar, Maftuch, Putra, & Risjani, 2019). Besides that, the three soft coral crude extracts showed DPPH scavenging properties at concentrations 10, 30, 50, 70, 90 g/mL (Tanod, Yanuhar, Maftuch, Wahyudi, & Risjani, 2019).…”
Section: Introductionmentioning
confidence: 63%
“…The previous study showed that DCM extracts of Sarcophyton spp. inhibited NO production [14]. This inhibition of NO production was presumably achieved by regulating the level of iNOS and its upstream molecules in LPS-induced macrophage cells [28].…”
Section: Discussionmentioning
confidence: 98%
“…The previous studies have also reported the ability of the dichloromethane (DCM) extract of Sarcophyton spp. (collected from Palu Bay, Central Sulawesi, Indonesia) to inhibit NO release [14]. In addition, soft coral Sarcophyton spp.…”
Section: Introductionmentioning
confidence: 99%
“…Metode broth-dilution berdasarkan pedoman EUCAST (2003) dan Wiegand et al (2008) (Tanod et al, 2019c). Rachmaniar (1995) menyatakan bahwa saponin merupakan metabolit dengan karakteristik rasa pahit dan bersifat toksik bagi amfibi dan ikan, serta memiliki fungsi farmakologis.…”
Section: Pengujian Antibakteri Dengan Metode Brothdilutionunclassified